2023
DOI: 10.3389/fped.2023.1115124
|View full text |Cite
|
Sign up to set email alerts
|

Association of volatile anesthesia exposure and depth with emergence agitation and delirium in children: Prospective observational cohort study

Abstract: BackgroundSevoflurane anesthesia is widely used in pediatric ambulatory surgery. However, emergency agitation (EA) and emergency delirium (ED), as major complications following sevoflurane anesthesia in children, pose risks to surgery and prognosis. Identifying the high risk of EA/ED, especially anesthesia exposure and the depth of anesthesia, may allow preemptive treatment.MethodsA total of 137 patients were prospectively enrolled in this single-center observational cohort study to assess the incidence of EA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…Another study demonstrated a relationship between the area under the curve of end-tidal sevoflurane concentration over time (EtSevo-time AUC) and ED. An EtSevo-time AUC of 2500–3000 in children showed a higher odds ratio (15.84) of agitation compared with lower EtSevo-time AUC values of 2000–2500 and ≤2000 (odds ratios: 3.99 and 1, respectively) [ 19 ]. We suspect that preoperative ingestion of clear liquids helped patients better cope with surgical stimuli by maintaining a euvolemic state compared to the fasting group.…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated a relationship between the area under the curve of end-tidal sevoflurane concentration over time (EtSevo-time AUC) and ED. An EtSevo-time AUC of 2500–3000 in children showed a higher odds ratio (15.84) of agitation compared with lower EtSevo-time AUC values of 2000–2500 and ≤2000 (odds ratios: 3.99 and 1, respectively) [ 19 ]. We suspect that preoperative ingestion of clear liquids helped patients better cope with surgical stimuli by maintaining a euvolemic state compared to the fasting group.…”
Section: Discussionmentioning
confidence: 99%